Cardiac Abnormalities in Children with Pre-Dialysis Chronic Kidney Disease in a Resource-Limited Setting: A Cross-Sectional Observational Study. (7th September 2021) - Bhagat, Naveen; Dawman, Lesa; Naganur, Sanjeev; Tiewsoh, Karalanglin; Kumar, Basant; Sharawat, Indar Kumar; Gupta, Krishan Lal
Abstract: Background: Cardiovascular disease is the leading cause of morbidity and mortality in children with chronic kidney disease (CKD). We aim to estimate the prevalence of cardiac abnormalities in children up to age 16 years with CKD and their association with various risk factors. Methods: This cross-sectional observational study was conducted on 107 CKD children. We assessed the systolic and diastolic function using 2D echocardiographic evaluation and M-mode measurements of the left ventricle (LV) indexed for BSA and z -scores were calculated. Results were compared with age, sex, stage of CKD, anaemia, estimated glomerular filtration rate (eGFR) and various laboratory parameters. Results: LV diastolic dysfunction was seen in 88%, followed by increased LV dimensions in 33.6%, LV systolic dysfunction in 16%, right ventricle systolic dysfunction in 11.2% while increased pulmonary artery (PA) systolic pressure was seen in 9.3% of cases. LV dimensions correlated directly with parathormone levels and inversely with eGFR, serum calcium and haemoglobin levels. Left ventricular hypertrophy correlated directly with parathormone while inversely with eGFR, serum calcium and haemoglobin. Ejection fraction directly correlated to eGFR and serum calcium while inversely related to parathormone. Left PA pressure directly correlated with age and inversely with eGFR. Right ventricular systolic function assessed by tricuspid annular plane systolic excursion correlated inversely with haemoglobin. Conclusion: LV diastolic dysfunction and increased LV dimensions were the most common cardiac abnormality in children with CKD. LV dimensions correlated directly with parathormone levels and inversely with eGFR, serum calcium and haemoglobin. Diastolic dysfunction positively correlated with serum creatinine and parathormone levels.